REKAYASA BUDAYA ORGANISASI 7 (TUJUH) KARAKTER UNIVERSITAS DHYANA PURA BALI - Komalasari, Yeyen (Buletin Studi Ekonomi; VOL.19.NO.2.AGUSTUS 2014.(PP 119-211), 2016)
Organizational Culture Engineering of The Seven Characters Dhyana Pura University Bali. Organizational culture can improve the behavior and motivation of human resources so as to develop their performance and in turn can increase organizational performance. Organizational culture can be created by the owner or head of the organization, according to the organization’s needs, as has been done by Dhyana Pura University by implementing a program called seven (7) characters to be an organizational culture. Culture of the organization will function optimally if all members of the organization have a common perception of the culture and are committed to implement it. Organizational culture can be a major instrument of competitive advantage, if it is supported and approved by all members of the organization. Strong organizational culture will be able to help in steering human resources to achieve the vision, mission and goals of the organization.   Keywords : culture organization, Undhira’s seven characters
Keywords: culture organization, Undhira’s seven characters